Auxin co-receptor IAA17/AXR3 controls cell elongation in Arabidopsis thaliana root solely by modulation of nuclear auxin pathway - Kubalová, Monika; Müller, Karel; Dobrev, Petre Ivanov; Rizza, Annalisa; Jones, Alexander M; Fendrych, Matyáš (The New phytologist, 2024)
The nuclear TIR1/AFB-Aux/IAA auxin pathway plays a crucial role in regulating plant growth and development. Specifically, the IAA17/AXR3 protein participates in Arabidopsis thaliana root development, response to auxin and gravitropism. However, the mechanism by which AXR3 regulates cell elongation is not fully understood. We combined genetical and cell biological tools with transcriptomics and determination of auxin levels and employed live cell imaging and image analysis to address how the auxin response pathways influence the dynamics of root growth. We revealed that manipulations of the TIR1/AFB-Aux/IAA pathway rapidly modulate root cell elongation. While inducible overexpression of the AXR3-1 transcriptional inhibitor accelerated growth, overexpression of the dominant activator form of ARF5/MONOPTEROS inhibited growth. In parallel, AXR3-1 expression caused loss of auxin sensitivity, leading to transcriptional reprogramming, phytohormone signaling imbalance and increased levels of auxin. Furthermore, we demonstrated that AXR3-1 specifically perturbs nuclear auxin signaling, while the rapid auxin response remains functional. Our results shed light on the interplay between the nuclear and cytoplasmic auxin pathways in roots, revealing their partial independence but also the dominant role of the nuclear auxin pathway during the gravitropic response of Arabidopsis thaliana roots.
Keywords: Arabidopsis thaliana; Gene Expression Regulation, Plant; kyseliny indoloctové; Indoleacetic Acids; ARF5/MP; AXR3-1; Arabidopsis Proteins; nuclear auxin pathway; regulátory růstu rostlin; Plant Roots; proteiny huseníčku; auxin; kořeny rostlin; cell elongation; IAA17/AXR3; regulace genové exprese u rostlin; cytoplasmic auxin pathway; Plant Growth Regulators; Arabidopsis